PTU-076 Sucrose intake increases the risk of developing pancreatic cancer: a UK prospective cohort study using data from food diaries. (23rd September 2015) - Banim, P J R; Luben, R; McTaggart, A; Wareham, N J; Khaw, K; Hart, A R
Abstract : Introduction: There are plausible biological mechanisms for how excess sucrose intake may initiate pancreatic carcinogenesis via an increased insulin release promoting cell proliferation. The aim of this study was to investigate dietary sucrose intake and the risk of pancreatic cancer, in a prospective cohort study using nutrient data from 7-day food diaries (7-DFDs). Methods: In EPIC-Norfolk (European Prospective Investigation into Cancer-Norfolk) 25 639 men and women aged 45–74 years were recruited between 1993 and 1997 and completed 7-DFDs. Participants' sucrose intake was calculated from these diaries using a computer programme containing information on 9000 food items. The cohort was monitored for 16 years to identify those who developed pancreatic cancer. Each case was matched with four controls, for age and gender, and conditional logistic regression used to calculate OR and 95% CI adjusted for smoking, diabetes and total energy intake. To look for threshold effect the OR was calculated comparing the highest quintile of sucrose intake with a combination of the lower four quintiles. Results: A total of 81 participants (51% men) developed pancreatic cancer (mean age=71.4 years SD=8.6 years) with a median sucrose intake of 44.2 grams per day (range 8.5–140.0 g/day). The highest compared to the lowest quintile intake of sucrose intake doubled the risk of pancreatic cancer, OR 2.27 (95% CI 0.90 to 5.74 p=0.08), with a trend across quintiles OR 1.23 (95% CI 0.99 to 1.53, p=0.07). Comparing the highest intake to a summation of the lowest four levels showed a positive association (OR 1.99, 95% CI 1.05 to 3.78, p=0.04). There was no effect for the intake of total sugars (trend across quintiles OR 0.98, 95% CI 0.77 to 1.26, p=0.90). Conclusion: The study showed a positive association of an increased sucrose intake with the risk of pancreatic cancer. These epidemiological findings support plausible mechanisms on how excess sucrose may stimulate pancreatic carcinogenesis. Sucrose intake should be accurately measured in future aetiological studies of pancreatic cancer.